Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan: Studi Pada Warung Bakso Bacit Pelanggan Perempuan di Parungponteng Tasikmalaya - Seli Yulianti; Dadang Munandar (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the influence of service quality and price on female customer satisfaction at Warung Bakso Bacit Parungponteng, Tasikmalaya. The research was motivated by a decline in customer numbers, complaints about service quality, and perceptions of inadequate pricing, which are suspected to influence customer satisfaction. The study used a quantitative method with a descriptive and verification approach. The sample consisted of 94 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with IBM SPSS. The results showed that service quality and price each had a positive and significant effect on customer satisfaction, and simultaneously had a positive and significant effect on customer satisfaction. These findings suggest that improving service quality and setting appropriate prices can increase female customer satisfaction at Warung Bakso Bacit Parungponteng.